2005
DOI: 10.1007/s00213-004-2078-1
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol-induced antidepressant-like effect in the Forced Swim Test is absent in estrogen receptor-β knockout (BERKO) mice

Abstract: These data suggest that E2-induced antidepressant-like effects in mice are mediated through activation of ER-beta. They offer preliminary support to the hypothesis that specific compounds acting at ER-beta may influence mood in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
119
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 58 publications
9
119
2
3
Order By: Relevance
“…Studies utilizing transgenic mice that do not express ERa and/or ERb demonstrate that knockout of these receptors throughout the lifespan have specific behavioral effects. ERb, but not ERa, knockout mice have increased anxiety and depressive behavior compared to their wild type counterparts (Krezel et al, 2001;Imwalle et al, 2005;Rocha et al, 2005;Walf and Frye, 2006a), but their reproductive behavior is intact (Ogawa et al, 1999). On the other hand, ERa knockout mice are infertile and are not sexually receptive when in contact with a sexually experienced male (Ogawa et al, 1998;Ogawa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies utilizing transgenic mice that do not express ERa and/or ERb demonstrate that knockout of these receptors throughout the lifespan have specific behavioral effects. ERb, but not ERa, knockout mice have increased anxiety and depressive behavior compared to their wild type counterparts (Krezel et al, 2001;Imwalle et al, 2005;Rocha et al, 2005;Walf and Frye, 2006a), but their reproductive behavior is intact (Ogawa et al, 1999). On the other hand, ERa knockout mice are infertile and are not sexually receptive when in contact with a sexually experienced male (Ogawa et al, 1998;Ogawa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus primarily expresses ERb (Shughrue et al, 1997;Shughrue and Merchenthaler, 2001). Studies in ERb knockout mice suggest that ERb is required for affective behavior as these mice have increased anxiety and depression behavior, which is not reversed by E 2 administration (Krezel et al, 2001;Imwalle et al, 2005;Rocha et al, 2005;Walf and Frye, 2006a). Administration of selective ER modulators (SERMs) that have greater affinity for ERb than ERa to ovx rats decrease anxiety and depressive behavior when administered subcutaneously or to the hippocampus Frye, 2005b, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies utilizing knockout mice or ERb SERMs suggest that E 2 's actions at ERb may be important for its antianxiety and antidepressant-like effects. ERb knockout mice have increased anxiety (Krezel et al, 2001), and do not have reduced anxiety or depression behavior in response to E 2 administration, as do their wildtype counterparts (Imwalle et al, 2005;Rocha et al, 2005;. S.c. administration of ERb, but not ERa, SERMs decrease anxiety and depressive behavior of OVX rats (Lund et al, 2005;Walf and Frye, 2005b;Walf et al, 2004).…”
Section: Neuropsychopharmacologymentioning
confidence: 97%
“…We selected these genes for two reasons: 1) our prior demonstration of the triggering of affective dysregulation in women with PMDD when exogenous estradiol was administered in the context of GnRH agonist-induced hypogonadism ; 2) recent studies identifying the importance of ER beta in animal models of anxiety and depression (Walf et al 2004;Krezel et al 2001;Rocha et al 2005) and of estrogen receptor alpha in arousal (Garey et al 2003). In addition, we examined associations with the Val158Met SNP (rs4680) in the gene for catechol-O-methyltransferase (COMT), an enzyme involved in estradiol metabolism, implicated in sex hormone-mediated cancer (Tanaka et al 2006;Sazci et al 2004), and observed in other studies to regulate activity in the prefrontal cortex, a brain region implicated as dysfunctional in PMDD (Rubinow et al in press).…”
mentioning
confidence: 99%